The Impact of Marriage Without a Guardian in the Perspective of Islamic Family Law and Indonesian Positive Law - Utami, Muna; Djawas, Mursyid; Amri, Aulil (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
Marriage without a legitimate guardian (wali) is a violation of both Islamic law and Indonesian positive law, which leads to various legal and social consequences. This study aims to analyze the case of a marriage without a wali that occurred in Gampong Simpang Peut, Kuala District, Nagan Raya Regency, and the impacts caused by such a marriage in the context of both Islamic law and Indonesian positive law. Using an empirical legal method and a qualitative approach, data was collected through observation, interviews, and literature study. The informants of the research included the Head of KUA (Office of Religious Affairs) in Kuala District, the Geuchik (village head) of Gampong Simpang Peut, Tuha Peut (village elders), and Tgk. Imum Meunasah Gampong Simpang Peut. The research findings indicate that the marriage without a legitimate wali that occurred in Gampong Simpang Peut is considered invalid according to Indonesian positive law, particularly based on Article 22 of Law No. 1 of 1974 on Marriage, which states that a marriage may be annulled if it does not fulfill the stipulated requirements, including the presence of a legitimate wali. Additionally, Article 71 (e) of the Compilation of Islamic Law (KHI) stipulates that a marriage conducted without a wali or with an unqualified wali is legally void. Social impacts arising from this include negative stigma toward the involved couple, conflicts between families, and legal uncertainties concerning the status of children born from the marriage. From an Islamic law perspective, marriage without a legitimate wali contradicts the principles of Islamic law, which requires the wali as an essential element of the marriage contract. According to the Shafi'i school of thought, marriage without a valid wali is considered fasid (defective) and invalid. This is further supported by Articles 14 and 19 of the KHI, which state that a marriage conducted without a legitimate wali can be annulled by the Religious Court. Furthermore, the Hadith of Prophet Muhammad SAW, which states, "There is no marriage except with a wali" (HR. Abu Dawood), emphasizes that the presence of a wali is a necessary condition for a valid marriage under Islam.